2017
DOI: 10.1038/s41598-017-17770-8
|View full text |Cite
|
Sign up to set email alerts
|

The celecoxib derivatives AR-12 and AR-14 induce autophagy and clear prion-infected cells from prions

Abstract: Prion diseases are fatal infectious neurodegenerative disorders that affect both humans and animals. The autocatalytic conversion of the cellular prion protein (PrPC) into the pathologic isoform PrPSc is a key feature in prion pathogenesis. AR-12 is an IND-approved derivative of celecoxib that demonstrated preclinical activity against several microbial diseases. Recently, AR-12 has been shown to facilitate clearance of misfolded proteins. The latter proposes AR-12 to be a potential therapeutic agent for neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 75 publications
(71 reference statements)
0
26
0
Order By: Relevance
“…We compared PrP C levels in C8D astrocytes with levels in a neuronal cell line derived from the peripheral nervous system (N2a), CNS-derived CAD5 cells, and immortalized MEFs. These cells were chosen because of their excellent susceptibility to prion infection (40,70). Our results revealed that PrP C mRNA levels in C8D astrocytes were comparable with that of N2a and MEF cells but lower than CAD5 cells.…”
Section: Discussionmentioning
confidence: 72%
“…We compared PrP C levels in C8D astrocytes with levels in a neuronal cell line derived from the peripheral nervous system (N2a), CNS-derived CAD5 cells, and immortalized MEFs. These cells were chosen because of their excellent susceptibility to prion infection (40,70). Our results revealed that PrP C mRNA levels in C8D astrocytes were comparable with that of N2a and MEF cells but lower than CAD5 cells.…”
Section: Discussionmentioning
confidence: 72%
“…To quantify the autophagic vacuoles, the background of images in the same series was filtered by the same threshold. Then, the “analyze particle” option of ImageJ was applied to quantify the mean fluorescence intensity, indicating the autophagy activity 18 .…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of a functional UPS, the autophagosomal-lysosomal pathway is known to target insoluble protein aggregates for degradation 11 . Inducing autophagy using trehalose 12 , lithium 13 , rapamycin 8 resveratrol 14 and celecoxib derivatives AR-12 15 has shown protection against prion infectivity in in vitro model systems. Furthermore, treatment with rapamycin and resveratrol has shown delayed disease onset in in vivo prion models 8 , 14 , although the precise mechanisms remain to be determined.…”
Section: Introductionmentioning
confidence: 99%